2021
DOI: 10.1016/s2213-2600(20)30459-8
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation management and clinical outcomes in invasively ventilated patients with COVID-19 (PRoVENT-COVID): a national, multicentre, observational cohort study

Abstract: Background Little is known about the practice of ventilation management in patients with COVID-19. We aimed to describe the practice of ventilation management and to establish outcomes in invasively ventilated patients with COVID-19 in a single country during the first month of the outbreak.Methods PRoVENT-COVID is a national, multicentre, retrospective observational study done at 18 intensive care units (ICUs) in the Netherlands. Consecutive patients aged at least 18 years were eligible for participation if t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
242
13
18

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(313 citation statements)
references
References 32 publications
24
242
13
18
Order By: Relevance
“…The final selection included 26 studies: 4 multicenter prospective cohort studies [17][18][19][20], 6 multicenter retrospective cohort studies [8,[21][22][23][24][25], 1 single center prospective cohort study [26], 1 multicenter prospective case series [27], 2 multicenter retrospective case series [28,29], 4 single center prospective case series [30][31][32][33] and 8 single center retrospective case series [34][35][36][37][38][39][40][41] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The final selection included 26 studies: 4 multicenter prospective cohort studies [17][18][19][20], 6 multicenter retrospective cohort studies [8,[21][22][23][24][25], 1 single center prospective cohort study [26], 1 multicenter prospective case series [27], 2 multicenter retrospective case series [28,29], 4 single center prospective case series [30][31][32][33] and 8 single center retrospective case series [34][35][36][37][38][39][40][41] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…It was also suggested that the mechanical ventilation of patients classified to these two clinical types of disease should also differ; those with stiff lungs should be ventilated in accordance with the recommendations for ARDS, and those with compliant lungs may be ventilated with higher tidal volumes (7-9 ml/kg ideal body weight) and lower PEEP (< 10 cmH 2 O) than recommended [49]. Subsequent studies conducted in larger patient populations did not confirm this observation [17,19,20,23,26]. Our review of the available literature, limited as it is to pooled data from multiple studies with different methodologies, also does not support the existence of a clinical dichotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, one cannot discriminate COVID-19 ARDS from classical ARDS on the basis of values of compliance. Moreover, studies now totalling well over 1000 patients with COVID-19 ARDS report values of compliance (27 mL/cm H 2 O, 1 35 mL/cm H 2 O, 2 28 mL/cm H 2 O, 3 and 32 mL/cm H 2 O 4 ) that are consistent or even lower than the values observed by Chiumello and colleagues (48 mL/cm H 2 O [SD 16] and 42 mL/cm H 2 O [14]) 5 , 6 and Gattinoni and colleagues (44 mL/cm H 2 O [17]) 7 in classical ARDS. In addition, Panwar and colleagues recently showed that patients with classical ARDS had a wide range of compliance, with about one in eight patients (136 [12·2%] of 1117 patients) having compliance of at least 50 mL/cm H 2 O, and that the ratio of partial pressure of arterial oxygen to fractional concentration of oxygen in inspired air (PaO 2 /FiO 2 ) and static compliance were almost completely dissociated.…”
mentioning
confidence: 99%
“…While it is true that this low infection fatality should reassure people that most infected individuals do not die, it should not be confused as a confirmation of a subjective impression (eg, possibly arising in people outside hospitals that only see asymptomatic/mildly symptomatic cases) that there is not an emergency and that individuals may soften the adoption of the necessary prevention and control measures to interrupt the spread of the disease. Indeed, if only a small percentage of patients are at risk of dying and require hospital care but many are infected in a very short window of time, the absolute number of those requiring admission may rapidly surpass the hospitals and intensive care units bed capacity, reducing quality of care and increasing fatality in patients with severe disease presentation (change of denominator), reaching values higher than 25%‐30% in intensive care units 9‐11 . This impression of a constantly severe disease may be the one of healthcare personnel caring for hospitalized COVID‐19 patients in highly affected areas, who everyday see several patients worsening and requiring invasive mechanical ventilation.…”
mentioning
confidence: 99%